The right to decent housing for the IDPs victims of the Colombian armed conflict, that live on Tunja - Reyes-Camargo, Mauricio (Universidad Pedagógica y Tecnológica de Colombia, 2015)
Forced displacement has become Colombia in one of the social problems of highest connotation that deserves attention for the multiple consequences due to omissions. For this reason it was required to investigate public policies developed by the municipality of Tunja, with regard to the satisfaction of thefundamental right to decent housing of the displaced victims of the armed conflict. This research was sustained in the approaches set out in the sentence T-025 of 2004, of the Constitutional Court, that sets a precedent based on the records generated in this field and with the subsequent unified sentences,as with continuous monitoring that has been given to this problem at the national level in those departments and municipalities with high presence of displaced people, where neither the department of Boyacá, nor the city of Tunja, appear in national statistics as recipients centers of displaced population, however, according to statistics from the Municipal Attorney of Tunja, are about 500 families. Despite the above and the multiplicity of court orders in pursuance of Sentence T-025 of 2004, the situation of the displaced people related to housing as a fundamental right, in the case of the resident  population in Tunja, remains very bad by the way so crude as the State through its various agencies, stole them 99 housing opportunities to the same number of families. It is worth to say that, in this case, the municipality is the responsible of this outrage.